2020
DOI: 10.18632/oncotarget.27572
|View full text |Cite
|
Sign up to set email alerts
|

Knock-down of the TIM/TIPIN complex promotes apoptosis in melanoma cells

Abstract: The Timeless (TIM) and it's interacting partner TIPIN protein complex is well known for its role in replication checkpoints and normal DNA replication processes.Recent studies revealed the involvement of TIM and TIPIN in human malignancies; however, no evidence is available regarding the expression of the TIM/TIPIN protein complex or its potential role in melanoma. Therefore, we investigated the role of this complex in melanoma. Toassess the role of the TIM/TIPIN complex in melanoma, we analyzed TIM/ TIPIN exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The yeast direct homolog Tof1 is a core component of the replicasome and is required for the S-phase DNA damage checkpoint, fork stalling during disturbed DNA replication, and fork pausing during replication disorders, whereas Tipin and its yeast direct homolog Csm3 have the same role as Tof1 in DNA synthesis [14,15]. Some studies have found that TIPIN is highly expressed in melanoma, knockdown of TIPIN inhibits melanoma proliferation and promotes apoptosis, and TIPIN depletion reduces tumorigenicity of melanoma xenografts in immunocompromised mice [8]. Similarly in triple-negative breast cancer samples mRNA levels of TIPIN were significantly higher than specimens from other breast cancer subgroups and healthy tissues, protein levels of TIPIN were able to make breast cancer subtypes more invasive and proliferative, and TIPIN depletion reduced the tumorigenicity of triple-negative breast cancer cells [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast direct homolog Tof1 is a core component of the replicasome and is required for the S-phase DNA damage checkpoint, fork stalling during disturbed DNA replication, and fork pausing during replication disorders, whereas Tipin and its yeast direct homolog Csm3 have the same role as Tof1 in DNA synthesis [14,15]. Some studies have found that TIPIN is highly expressed in melanoma, knockdown of TIPIN inhibits melanoma proliferation and promotes apoptosis, and TIPIN depletion reduces tumorigenicity of melanoma xenografts in immunocompromised mice [8]. Similarly in triple-negative breast cancer samples mRNA levels of TIPIN were significantly higher than specimens from other breast cancer subgroups and healthy tissues, protein levels of TIPIN were able to make breast cancer subtypes more invasive and proliferative, and TIPIN depletion reduced the tumorigenicity of triple-negative breast cancer cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…TIM-interacting protein (TIPIN) is a 301-aa protein that interacts with TIM (TIMELESS) and was originally discovered in yeast [7]. A current study found that TIPIN is aberrantly expressed in melanoma and triple-negative breast cancer, and that low levels of TIPIN promote apoptosis in melanoma and triple-negative breast cancer [8,9]. However, no study has yet found whether there is a relationship between TIPIN and the development of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of the TIPIN expression induced apoptosis and inhibited proliferation in breast cancer cell lines, making TIPIN a potential target for breast cancer therapy [32]. Furthermore, knockdown of the TIM-TIPIN complex has been reported to promote apoptosis in melanoma cell lines [33]. However, because of the limited conditions, we could not conduct molecular, cellular, and animal experiments; therefore, the Disease Markers 13 Disease Markers specific molecular mechanism of TIPIN in the progression of HCC remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%